Soft Skills and Employability of Online Graduate Students - Alejandra Bedoya-Guerrero; Andrea Basantes-Andrade; Francisco Orlando Rosales; Miguel Naranjo-Toro; Rocio León-Carlosama (MDPI AG, 2024)
In the current context, with the growing influence of Artificial Intelligence, soft skills emerge as a crucial and distinctive factor for professionals. This research focuses on assessing the relationship between soft skills and their importance in the employability of online graduate students. A mixed methodological, non-experimental and explanatory level approach was used; a sample of 192 online graduate students from a university in northern Ecuador was analyzed. Data collection was carried out through an online survey, validated with a Cronbach's Alpha coefficient of 93.2%. The survey addressed socioeconomic data and the evaluation of soft skills through a 30-question questionnaire with a five-point Likert scale. According to the students' perception, the soft skills most in demand for employability are leadership and teamwork. After the reduction of dimensions using multiple correspondence analysis (MCA), respondents were classified into three clusters. Individuals in clusters one and three developed soft skills such as self-regulation, effective communication, leadership and innovation.